Harnessing The Power of English Songs in ELT Classrooms: A Review of Pedagogical Impacts Across Educational Levels - Marisa Linia; Yuni Putri Utami; Awati Fane; Achmad Faqih; Moh. Taufik (Jurnal Intelek Insan Cendikia, 2025)
The integration of songs into English Language Teaching (ELT) has gained increasing attention as an engaging and effective instructional approach. This literature review explores the role of English songs as instructional media in enhancing students’ language skills across various educational levels. Drawing on studies published between 2011 and 2021 from databases such as Google Scholar and Publish or Perish, the review focuses on how songs contribute to the development of listening, speaking, vocabulary, pronunciation, and learner motivation. The analysis is organized according to three educational contexts: junior high school, senior high school, and higher education. Findings suggest that the use of English songs can foster a positive learning atmosphere, reduce learners’ anxiety, and improve engagement and skill acquisition. The review highlights the pedagogical value of songs in ELT and provides practical insights for educators seeking to implement song-based strategies in their classrooms